Burst Motor Cortex Stimulation Evokes Sustained Suppression of Thalamic Stroke Pain: A Narrative Review and Single-Case Overview - Nuessel, Martin; Hamperl, Melanie; Maslarova, Anna; Chaudhry, Shafqat R.; Kohn, Julia; Stadlbauer, Andreas; Buchfelder, Michael; Kinfe, Thomas Mehari (Pain and Therapy, 2020)
Chronic refractory central post-stroke pain (CPSP), one of the most disabling consequences of cerebral stroke, occurs in up to 10% of patients with CPSP. Because a considerable proportion of these patients with chronic pain remain resistant to pharmacological and behavioral therapies, adjunctive invasive and non-invasive brain stimulation therapies are needed. We performed a review of human studies applying burst and conventional motor cortex stimulation (burstMCS and cMCS, respectively) for chronic pain states, on the basis of data sources identified through searches of PubMed, MEDLINE/OVID, and SCOPUS, as well as manual searches of the bibliographies of known primary and review articles. Our aim was to review and discuss clinical data on the indications of burstMCS for various chronic pain states originating from central stroke (excluding trigeminal facial pain). In addition, we assessed the efficacy and safety of burst versus cMCS for central post-stroke pain with an extended follow-up of 5 years in a 60-year-old man. According to our review, uncontrolled observational human cohort studies and one RCT using cMCS waveforms have revealed a meaningful clinical response; however, these studies lacked placebo groups and extended observation periods. In our case report, we found that 3 months of adjunctive cMCS reduced pain levels [visual analog scale (VAS) pre: 9/10 versus VAS post 7/10], whereas the pain decreased further under burstMCS (VAS pre: 7/10 versus VAS post: 2/10); the study involved a follow-up of 5 years and the following parameters: burst rate 40 Hz (500 Hz), 1-1.75 mA, 1 ms, bipolar configuration. To date, only limited evidence exists for the efficacy and safety of burst motor cortex stimulation for the treatment of refractory chronic pain. BurstMCS resulted in significantly decreased post-stroke pain observed after 5 years of cMCS. The available literature suggests similar efficacy as that of conventional (tonic) motor cortex stimulation, although the results are preliminary. Mechanistically, the precise mechanism of action is not fully understood. However, burstMCS may interact with the nociceptive thalamic-cingulate and descending spinal pain networks. To determine the potential utility of this treatment, large-scale sham-controlled trials comparing cMCS and burstMCS are highly recommended.
CRIS-Team WoS Importer:2021-01-01